FRI0049 Significant improvement of rheumatoid arthritis (RA) outcome with repeated self-assessment applying smart system of disease management (SSDM) mobiles tools: a cohort study of ra patients empowering. (12th June 2018) - Yang, J.; Huang, J.; Wang, Y.; Wei, H.; Mu, R.; Fan, W.; Wang, H.; Duan, X.; Shi, X.; Zhang, Y.; He, F.; Xue, J.; et al.
Abstract : Background: Treat-to-Target (T2T) strategy are critical for the treatment of RA, but the Chinese rheumatologists can hardly provide patients with a complete assessment in the clinic due to limited time. The SSDM includes interfaces of both physicians' and patients' application. After inputting lab test records, treatment regiments, and executing DAS28 assessment by patients themselves, all data can be synchronised automatically to the authorised physicians' mobile tool. The rheumatologists can adjust treatment regiments base on patients' profile. Our previous study showed that patients in China can master the application of SSDM for accurately evaluating DAS28 and health assessment questionnaire (HAQ) after training. Objectives: The objective of this study is to explore the effectiveness of applying SSDM in improvement of disease activity after repeated self-assessment in Chinese RA patients. Methods: Patients were trained to do DAS28 evaluation with SSDM and asked to repeat the self-assessment once a month. Descriptive statistics were performed for patient and disease characteristics. According to DAS28 scores, disease activity, the cohort was divided into four groups: remission (Rem), low disease activity (LDA), moderate disease activity (MDA) and high disease activity (HDA).T2T, achieving a DAS28 score lower than 2.6 (Rem) or below 3.2 (LDA), is the main management strategy recommended by ACR and EULAR. Results: From Jun 2014 to, Jan 2018 a total of 24, 731 RA patients from 486 centres in China participated in the study. The mean age was 49.28±16.08 (18 to 99) years and the median disease duration was 18.30 months. All patients performed self-assessment of DAS28, HAQ and morning stiffness time totally for 30 358 times. Proportion of patients in Rem, LDA, MDA and HDA was 18%, 13%, 45% and 24% respectively at baseline. Of which, 3492 patients performed repeated assessment for 11 251 times. Proportion of patients in Rem, LDA, MDA and HDA changed into 44%, 18%, 31% and 7% at the last assessment. The proportion of T2T at the last assessment was significantly higher than that of baseline significantly (p<0.001). According to the assessments, the rate of T2T from baseline to 3 months, 6 months, 9 months, 12 months and over 12 months were 31%, 47%, 56%, 58%, 61% and 62% (see figure 1). With the increase of the times of self-assessment, the T2T rate was significantly improved (p<0.001). Conclusions: Under repeated self-assessment of DAS28 using SSDM, RA patients can achieve better T2T result. Though empowering patients, SSDM can assist rheumatologist to rationally adjust treatment for RA patients. Disclosure of Interest: None declared